First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations The PEOPLE'S LEAGUE of HEALTH (INCORP.) "A Nation's Health is a Nation's Wealth" [photograph] Photo H. Craely, Metropole Studios, Cardiff List of Founders: HIS MAJESTY THE KING MRS. BROWN OF KNOCKBREX THE RT. HON. VISCOUNT BURNHAM THE RT. HON LADY BYRON D.B.E. LT.-COL. J.A. INNES, D.S.O. LADY KENT THE RT. HON. THE LORD LEVERHULME MISS OLGA NETHERSOLE, R.R.C. THE RT. HON. VISCOUNT NORTHCLIFFE THE LATE MRS. GORDON SELFRIDGE MR. H.L. STOREY MR. A.R. THOMSON SIR BASIL ZAHAROFF, G.C.B., G.B.E. 200/B/3/2/C693/1/71